Superstars in the National Basketball Association: Economic Value and Policy - Hausman, Jerry A.; Leonard, Gregory K. (Journal of Labor Economics, 1997)
An econometric analysis demonstrates that television ratings for NBA games are substantially higher when certain players ('superstars') are involved. Thus, these superstars are quite important for generating revenue, not only for their own teams but for other teams as well. Using the econometric analysis and additional information on attendance and paraphernalia sales, the authors estimate the value of Michael Jordan to the other NBA teams to be approximately $53 million. The positive externality superstars have on other teams can lead to an inefficient distribution of player talent. The authors examine several league policies that might be used to address the externality. Copyright 1997 by University of Chicago Press.